Identification of Vinculin as a Potential Plasma Marker for Age-Related Macular Degeneration - Kim, Hye-Jung; Woo, Se Joon; Suh, Eui Jin; Ahn, Jeeyun; Park, Ji Hyun; Hong, Hye Kyoung; Lee, Ji Eun; Ahn, Seong Joon; Hwang, Duck Jin; Kim, Ki Woong; Park, Kyu Hyung; Lee, Cheolju (ASSOC RESEARCH VISION OPHTHALMOLOGY INC, 2014)
PURPOSE. To identify plasma protein biomarkers for age-related macular degeneration (AMD) using a large-scale quantitative proteomic discovery procedure. METHODS. Plasma proteomes from 20 exudative AMD patients and 20 healthy control patients were comparatively profiled by four-dimensional liquid chromatography-tandem mass spectrometry (LC-MS/MS). Proteins existing at statistically different levels were validated by enzyme-linked immunosorbent assay (ELISA) and Western blotting in 233 case-controlled samples. Newly discovered plasma biomarkers were further confirmed using in vivo and in vitro experiments. RESULTS. Out of 320 proteins identified, vinculin, protein S100A9, triosephosphate isomerase, protein S100A8, protein Z-dependent protease inhibitor, C-X-C motif chemokine 7, and tenascin X showed significantly differential expression in AMD patient plasma compared to control plasma. Among these, the area under the curve (AUC) for vinculin was 0.871 for discriminating between exudative AMD and controls (n = 201) and 0.879 for discriminating between AMD and controls (n = 233). A proteogenomic combination model using vinculin and two known risk genotypes in ARMS2 and CFH genes additionally provided excellent discrimination of AMD from controls (AUC = 0.916). The plasma level of vinculin was not associated with any confounding clinical variables, such as age, smoking, and other comorbidities. Additionally, vinculin was strongly expressed in retinal pigment epithelial cells of human eyes, and its expression was elevated when exposed to oxidative stress in vitro. CONCLUSIONS. Vinculin was identified as a potential plasma biomarker for AMD. The early detection of AMD using novel plasma biomarkers with genetic modeling may enable timely treatment and vision preservation in the elderly.
Keywords: RETINAL-PIGMENT EPITHELIUM; PROTEOME-PROJECT; PROTEINS; COMPLEX; S100A9; PATHOGENESIS; PREVALENCE; EXPRESSION; BIOMARKERS; CANCER